ANALISIS YURIDIS KEKUATAN PEMBUKTIAN OLEH ANAK SEBAGAI SAKSI KORBAN DALAM TINDAK PIDANA PERKOSAAN (Studi Putusan Nomor: 71/Pid.B/2017/PN.Mre) - Grace Hanin; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In the mere of criminal acts, a child does not only become a victim. It can be found in suchcases that a child is also being the witness of a crime that has happened. This is based on LawNumber 11 of the year 2012 concerning the Juvenile Criminal Justice System in Article 1 number 2which states that Children in Conflict with the Law are children in conflict with the law, childrenwho are victims of criminal acts, and children who are witnesses of criminal acts. Witnesstestimony is the most important evidence in a case. However, children under the age of 15 are notconsidered to be witnesses who are sworn (taken oath) in an attempt to testify in court. Eventually,the child does not become evidence of witness testimony which is considered valid in proving acriminal case.The purpose of this thesis is: First, to analyze how far is the proofing that is stated by achild in the effort of solving the crime of rape (case of Verdict Number: 71/Pid.B.2017/Pn.Mre).Second, to analyze the type of special protection that can be given to a child victim who witnessedthe crime of rape. The research that is used in writing this thesis is Normative Juridical ApproachMetho or Literature Study in order to obtain secondary data. To obtain secondary data, researcherstudies and analyzes the laws and regulations, law theories to sum up the conclusion of a matterthat is being examined.From the results of the study, there are 2 (two) main things that can be concluded: First, Achild who is not yet 15 (fifteen years) of age cannot be taken an oath or promise in giving his/hertestimony in court. However, as long as there is a match between the child’s statement and otherlegal evidence, the child’s statement can be classified as a guide that can be the basis instrengthening the Judge’s beliefs in making a final decision. Second, The child in providing his/herstatement may also disclose his/her statement outside of the court’s session, namely throughelectronic recording carried out by the Local Community Counselor, in the presence ofInvestigators or Public Prosecutors, and Advocates or other legal aid providers that is involved inthe existing case. Child witnesses and/or child victims are also allowed to provide informationthrough remote examination using audiovisual communication tools. All of this is done in order tomaintain good protection for children in law.The legal position of a child in the effort of proofing a crime is frankly stated in theCriminal Code of Indonesia, yet according to the legislatives that somebody who is still categorizedas a child does not have the perfect responsibility and accountability in the purpose of givingtestimonials in trial. Therefore, a child’s testimony is used either as a “clue” or addition of a validmeans of evidence which is also useful to convince the Judge in trial.The researcher’s suggestion is that in making a decision that is as fair as possible, theJudge(s) should be wise when considering the evidence that are also obtained from the factsrevealed before the trial. Even though the victim witnesses are classified as “children” and tend toJOM Fakultas Hukum Universitas Riau Volume IX Edisi 2 Juli – Desember 2022 Page 2be in the unstable state of self, may the information from the statement given by the child remains aconsideration that has strong value considering that in a rape crime, the child is the only victimwho directly experienced and witnessed the crime of rape by the perpetrator.Keywords : Child-Child Witness-Crimes-Rape